1999
DOI: 10.1152/ajpheart.1999.277.2.h533
|View full text |Cite
|
Sign up to set email alerts
|

Microembolization in pigs: effects on coronary blood flow and myocardial ischemic tolerance

Abstract: Coronary microembolization has been reported to increase coronary blood flow (CBF) through adenosine release. Because adenosine may increase ischemic tolerance against infarction, we tested the hypothesis that myocardial microembolization, a common finding in patients with ischemic heart disease, induces cardioprotection. Additionally, because the use of microspheres is a common tool to measure tissue perfusion, the effects of small amounts of microspheres on CBF were examined. Using anesthetized pigs, we meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 52 publications
1
10
0
1
Order By: Relevance
“…It has been reported that the microembolized myocardium is characterized by perfusion-contraction mismatch, reduced contractile function and unchanged or possibly elevated blood flow. [17,18] Since cardiomyocytes are non-renewable cells, the loss of cardiomyocytes via apoptosis may play an important role in the progression of myocardial contractile dysfunction. The mechanisms of myocyte cell death include apoptosis and necrosis, with early research confirming that myocyte cell death by apoptosis is likely in the beginning hours of ischemia, and that myocyte cell death by necrosis is evident after long-term ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the microembolized myocardium is characterized by perfusion-contraction mismatch, reduced contractile function and unchanged or possibly elevated blood flow. [17,18] Since cardiomyocytes are non-renewable cells, the loss of cardiomyocytes via apoptosis may play an important role in the progression of myocardial contractile dysfunction. The mechanisms of myocyte cell death include apoptosis and necrosis, with early research confirming that myocyte cell death by apoptosis is likely in the beginning hours of ischemia, and that myocyte cell death by necrosis is evident after long-term ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Wiederholte intrakoronare Injektionen (Enddosis 3 000 Mikrosphären pro ml/min koronaren Einstroms) bewirken unmittelbar nach jeder Injektion eine transiente Reduktion der Koronardurchblutung, der eine länger andauernde reaktive Durchblutungserhöhung folgt (Abbildung 1). Grund für die Zunahme der Koronardurchblutung nach Mikroembolisation, trotz mechanischer Verlegung des Gefäßbetts durch Embolisationspartikel, ist die Freisetzung vasodilatatorischer Mediatoren, die in benachbarten Gefäßen eine Vasodilatation bewirkt [19,26]. Im Gegensatz zur Koronardurchblutung erholt sich die myokardiale Funktion nach jeder Injektion nur teilweise und wird mit jeder erneuten Mikroembolisation immer mehr reduziert (Abbildung 1) [35].…”
Section: Experimentelle Koronare Mikroembolisation Als Modell Einer Iunclassified
“…Subsequently, myocardial function is progressively reduced whereas coronary blood flow remains unchanged or is even increased (perfusion -contraction mismatch) [2,3]. The increase in coronary blood flow is attributed to vasodilation of adjacent nonembolized vessels in response to adenosine release from the ischemic microembolized myocardium [4,5]. The progressive myocardial contractile dysfunction in the presence of normal or increased blood flow following microembolization is associated with an inflammatory response, characterized by increased leukocyte infiltration and increased tumor necrosis factor-a (TNFa) concentration within the myocardium [2].…”
Section: Introductionmentioning
confidence: 99%
“…This adenosine dilates vessels in the adjacent non-embolized myocardium and increases myocardial blood flow [4,5]. Adenosine is an important trigger of ischemic preconditioning (IP) in many species including pigs [8] and also humans [9].…”
Section: Introductionmentioning
confidence: 99%